2021
DOI: 10.1111/asj.13666
|View full text |Cite
|
Sign up to set email alerts
|

Improving growth performance and blood profile by feeding autolyzed yeast to improve pork carcass and meat quality

Abstract: The 63 commercial pigs were divided into three groups consisting of seven replicates of three piglets each. The experimental diets were (1) control diet, (2) diet with autolyzed yeast (AY) 0.5%, and (3) diet with AY 1.0%. Compared to the control group, using AY 0.5% in the diet reduced average daily feed intake (ADFI) and improved feed conversion ratio (FCR) (p < 0.05). The blood urea nitrogen (BUN) and neutrophil/lymphocyte ratio (N/L) in blood decreased with the addition of AY 0.5% (p < 0.05). The pH at 6‐h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…In this study, we found that dietary YC supplementation significantly decreased the TP, ALB, and urea nitrogen levels on day 60. Meanwhile, Namted et al [ 3 ] reported that BUN decreased with the addition of 0.5% autolyzed yeast. Pigs fed diets containing mycotoxins and yeast cell wall extract showed increased apparent ileal digestibility of crude protein, and the GE of nursery piglets [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that dietary YC supplementation significantly decreased the TP, ALB, and urea nitrogen levels on day 60. Meanwhile, Namted et al [ 3 ] reported that BUN decreased with the addition of 0.5% autolyzed yeast. Pigs fed diets containing mycotoxins and yeast cell wall extract showed increased apparent ileal digestibility of crude protein, and the GE of nursery piglets [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the GRA-based diet and YC tended to improve the meat quality of finishing pigs. Namted et al [ 3 ] reported that 0.5% autolyzed yeast in the diet of pigs increased their springiness and tended to increase the redness and pH of the meat at 6 h postmortem. The improvement in beef tenderness following active dry yeast supplementation of finishing bulls is related to an increase in the level of CAT in the serum and glutathione reductase in the meat [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of AY has been summarized as: 3.5-3.9% nucleic acids, 11-22% of β-glucan, 3-12% MOS, 30.0-41.1% crude protein, and 2.51-5.00 % crude fat (Berto et al, 2020;Namted et al, 2021). Using 0.2-0.5% AY as a feed additive in pig diets seemed to improve the performance and immune function of weaned and finished pigs (Upadhaya et al, 2019;Berto et al, 2020;Namted et al, 2021) (Table 2).…”
Section: Autolyzed Yeast (Ay)mentioning
confidence: 99%